A top-down synthesis of wurtzite Cu2SnS3 nanocrystals for efficient photoelectrochemical performance. Issue 18 (24th April 2018) - Sun, Weijun; Ye, Yangwei; You, Yu; Xu, Jun
Abstract : Wurtzite Cu2 SnS3 nanocrystals are synthesized through a green hydrothermal method based on a top-down strategy and are further demonstrated as a promising sensitizer for efficient photoelectrochemical water splitting. Abstract : In this work, a top-down strategy to prepare metastable wurtzite Cu2 SnS3 nanocrystals is reported for the first time. Wurtzite Cu2 SnS3 nanocrystals with diameters of 7± 3 nm are synthesized by reacting Cu2 O nanocubes in a tin–metal chalcogenide complex (Sn–MCC) aqueous solution. A conversion process of cubic Cu2 O nanocubes→ monoclinic Cu7 S4 nanoboxes→ hexagonal CuS nanoboxes→ wurtzite Cu2 SnS3 nanoboxes→ wurtzite Cu2 SnS3 nanocrystals is systematically investigated. It is revealed that formation of hollow nanoboxes is resulted from the Kirkendall effect while evolution from Cu2 SnS3 nanoboxes to tiny Cu2 SnS3 nanocrystals is due to an etching effect. Cu2 SnS3 nanocrystal sensitized ZnO nanorod arrays are demonstrated as efficient photoanodes for photoelectrochemical (PEC) water splitting. Our work opens up a new door to prepare ecofriendly chalcogenide nanocrystals and for their promising applications in solar energy conversion devices.